Church as Infirmary (16100680847) - Miami University... (Wikimedia Commons, 2015)
Carte postale ancienne issue de Wikimedia Commons. Titre: Church as Infirmary (16100680847). Persistent URL: digital.lib.miamioh.edu/cdm/compoundobject/collection/pos... Subject: World War I | Churches | Infirmaries | Wounds & injuries | France–Cierges | miami digital collections | bowden postcard collection
Licence No known copyright restrictions via Wikimedia Commons
Keywords: carte postale; image; patrimoine; histoire locale; wikimedia commons; église